ETHICAL DILEMMA - A PATHWAY TO FRAUD OR NOT? - Ćerdić, Ivan Mate; Knežević, Goranka (The European Journal of Applied Economics, 2023)
Financial fraud committed by employees is a phenomenon that has been present in business and professional circles for a long time, however, with the advent of increasingly sophisticated techniques for doing so, the real challenge is how to prevent fraud. The aim of this research is to prove that when the opportunity arises to commit financial fraud, ethical principles and codes of conduct go beyond the personal and collective motives of employees. Furthermore, we try to confirm that constant training of employees on the topic of the code of ethics reduces the possibility of financial fraud in the company. To find the evidence to support our research questions, a survey was conducted in the form of a questionnaire, while the respondents were employees from the sectors of Accounting, Finance, Auditing, as well as graduate students in the fields of Accounting, Auditing and Management in major cities in the Republic of Serbia. The research results showed that almost 50% of respondents never get training in the area of code of ethics application in real life cases and 20-30% remain undecided on each ethical dilemma presented in the questionnaire, therefore confirming our hypothesis that there is a much room to implement ethical training as the most important prevention technique for fraud in Serbian companies.